Characteristics of CNG bubbles in Diesel flow under the influence of the magnetic field - Abdul Wahhab, H. (Isfahan University of Technology, 2017)
This paper conducts an analytic study of the hydrodynamics of a small CNG bubbles in laminar horizontal Diesel flow under the influence of the magnetic field. Investigation based on experiments was carried out to identify the effects caused by varying the magnetic field intensity on the trajectory, the formation of bubbles and their shape and velocity. Different images at different positions were captured through a high speed camera, image processing technique and downstream from the CNG bubbles injection point delivered information on bubble velocity, bubbles size, spatial location and gas area fraction as a function of changing magnetic field intensity. The outcomes confirmed that CNG bubbles under magnetic field grow up vertically to have a bigger elliptical shape in the Diesel phase with the twofold of diameter. Also, it has been noted that the CNG bubbles velocity decreased as the magnetic field strengthened.